Manfaat Data Warehouse Pada PT ABC - M., Evaristus Didik; S., Dewi; L., Felisia; S., Winnie (Bina Nusantara University, 2013)
The purpose of this paper is to analyze the current system to find out problems faced by the company and propose alternative solutions and generate information needed by management by designing a data warehouse according to the information needs of PT ABC. This research implements analysis and design of datawarehouse by Ralph Kimball and Ross cited by Connolly and Begg, known as Nine-Step Methodology. The result obtained is a data warehouse application that may present a multidimensional historical data that can assist the management in decisions. Designing data warehouse at PT ABC makes concise the enterprise dataand can be viewed from several dimensions. It helps users analyze data for strategic decision quickly and accurately.